Controlling the AP Controller: Controller Performance Assessment and Modification. (November 2019) - Hajizadeh, Iman; Hobbs, Nicole; Samadi, Sediqeh; Sevil, Mert; Rashid, Mudassir; Brandt, Rachel; Askari, Mohammad Reza; Maloney, Zacharie; Cinar, Ali
Background: Despite recent advances in closed-loop control of blood glucose concentration (BGC) in people with type 1 diabetes (T1D), online performance assessment and modification of artificial pancreas (AP) control systems remain a challenge as the metabolic characteristics of users change over time. Methods: A controller performance assessment and modification system (CPAMS) analyzes the glucose concentration variations and controller behavior, and modifies the parameters of the control system used in the multivariable AP system. Various indices are defined to quantitatively evaluate the controller performance in real time. Controller performance assessment and modification system also incorporates online learning from historical data to anticipate impending disturbances and proactively counteract their effects. Results: Using a multivariable simulation platform for T1D, the CPAMS is used to enhance the BGC regulation in people with T1D by means of automated insulin delivery with an adaptive learning predictive controller. Controller performance assessment and modification system increases the percentage of time in the target range (70-180) mg/dL by 52.3% without causing any hypoglycemia and hyperglycemia events. Conclusions: The results demonstrate a significant improvement in the multivariable AP controller performance by using CPAMS.